STRATEGI PENINGKATAN PARIWISATA DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG TAHUN 2010-2015 - Zahra Ferlanika; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2017)
Tourism sector is now being regarded as an important development program because of its position as a source of income. There are four travel destinations managed by Semarang Culture amd Tourism Department, each of which have a uniqueness. By utilizing a strategic place, Semarang Government designs a concept to increase tourism which consists of several stratehies. But the management of the tourism increasing strategy by Culture and Tourism Department is still not optimal. Therefore, this study is conducted to find out how is the tourism increasing strategy done by Semarang Culture and Tourism Department. This study used a qualitative descriptive method and SWOT analysis with documentation and interview as the means to collect data. The target of this study is government, specifically Semarang Culture and Tourism Department and people participating in the management of Semarang's tourist attractions. Strategy is defined as steps or methods done by the government in a long term to achieve an objective. Based on the result of this study, the problems faced by Semarang Culture and Tourism Department in general regarding the strategy to increase tourism include the facilities and infrastructure that had not been ideal, limited budget, the quality and quantity of HR that is still lacking, and the lack of events that can have a high value, and thus hamper an improvement in tourism. This study encourages tourism stakeholders to pay attention to the strategy discussed in this study. There is a need for government, private, and public’s involvement, improvement in HR quality and quantity, construction of facilities and infrastructures that are felt to be lacking, and also a good teamwork between the parties involved in improving the tourism sector in Semarang.